Investigation of heat transfer in dimple-protrusion micro-channel heat sinks using copper oxide nano-additives. (December 2021) - Khan, Muhammad Zia Ullah; Akbar, Bilal; Sajjad, Ramisha; Rajput, Umair Ahmed; Mastoi, Sanaullah; Uddin, Emad; Hussain, Azhar; Younis, Md Yamin; García Márquez, Fausto Pedro; Akram, Naveed
Abstract: The ability of controlling the temperature of a system by using heat transfer and thermodynamics-based technology is known as thermal management. Thermal management is a crucial problem which is to be addressed in the various fields. This study accompanies a numerical work to provide a solution for heat transfer enhancement by studying a straight rectangular cross-section channel. The selected channel is used with and without disturbance in the form of dimple-protrusion with circular & through geometry. Water is employed as the base fluid for identifying flow behavior and heat carrying capacity while the heat flux is applied as a boundary condition. Furthermore, using the same boundary condition, copper oxide nanoparticles with the concentration of 0.10%, 0.15% and 0.20% respectively are added in the channels. Flow conditions are varied from 100 to 900 considering the laminar regime with fully developed flow. Performance enhancement criteria are evaluated by considering the Nusselt number, friction factor, and base cooling. The fully developed velocity profile is maintained at the inlet of test section for all Reynolds numbers. Semi-Implicit Method for Pressure Linked Equations (SIMPLE) pressure-velocity coupling is used with the second-order upwind scheme for discretization and solution approximation. It is observed that circular dimple-protrusion channel is effective for high Reynolds numbers and through dimple protrusion is efficient for intermediate Reynolds numbers. 10% improvement in Nusselt number is observed for circular dimple-protrusion channel with 0.2% CuO concentration by comparing the results of dimple-protrusion channel with straight channel at same nanoparticle concentration. Compared to straight channel with 0% and 6% particles concentration 5% and 7% increase in Stanton number is observed for through disruption case. Dimple channel on the other hand showed 3% and 5% increase. Furthermore, the formation of vortices at high Reynolds number is observed in circular dimple-protrusion channel. Highlights: We analyzed dimple-protrusion effect in circular and through width form on heat transfer performance. The effect of copper oxide nano-additive on heat transfer and friction factor of the different geometries channel is also investigated. Thermal Performance Factor is used to identify the optimum performance channel. The circular disruption channel is found more effective at high Reynolds number due to flow expansion and contraction. The through dimple protrusion channel is found effective for all particle's concentration compared to circular due to higher temperature gradients.